Karyotypic Data on 28 Species of Scinax (Amphibia: Anura: Hylidae): Diversity and Informative Variation - Cardozo, Dario E.; Leme, Daniela M. [UNESP]; Bortoleto, Joao F. [UNESP]; Catroli, Glaucilene F. [UNESP]; Baldo, Diego; Faivovich, Julian; Kolenc, Francisco; Silva, Ana P. Z.; Borteiro, Claudio; Haddad, Celio Fernando Baptista [UNESP]; Kasahara, Sanae [UNESP] (Amer Soc Ichthyologists & Herpetologists, 2011)
The hylid frog genus Scinax is the most species-rich within Hylinae, with more than 100 recognized species grouped in the S. catharinae and S. ruber clades. The karyotypes of 14 species of the S. catharinae clade and 14 of the S. ruber clade were analyzed, several of them for the first time. All studied species presented 2n = 2x = 24 biarmed chromosomes (FN = 48) and no identifiable sex chromosomes. There are two alternate states associated with the size and morphology of pair 1, corresponding to the S. catharinae clade and to the S. ruber clade. The morphology of pairs 2 and 6 also differentiate the species of both major clades. Species of the S. ruber clade in general have Ag-NORs in pair 11, as is commonly observed among hylines with 2n = 24. The Ag-NORs' position in the long arms of pair 11 is interstitial in S. fuscomarginatus, S. fuscovarius, S. nasicus, S. similis, S. squalirostris, and S. uruguayus, and terminal in S. acuminatus, S. curicica, S. duartel, S. granulatus, S. hayii, and S. perereca. The single exception among species of the S. ruber clade is S. alter, which has terminal Ag-NORs at the long arms of pair 3. Most species of the S. catharinae clade have Ag-NORs in pair 6, representing a putative synapomorphy of this clade, while the Ag-NORs in pair 11 that occur in S. canastrensis are most parsimoniously interpreted as a reversion. C-banding is predominantly centromeric, but in the S. catharinae clade there is a greater amount of heterochromatin than in the S. ruber clade. This study corroborates the occurrence of informative variation, some already considered in a previous cladistic analysis, and reports new characters, outlining the significance of cytogenetic data for the systematics of Scinax.